Smallholder farmers’ participation in profitable value chains and contract farming : Evidence from irrigated agriculture in Egypt - Tabe-Ojong, Martin Paul Jr.; Abay, Kibrom A. (International Food Policy Research Institute, 2023)
Key messages The participation of smallholder farmers in high-value and profitable value chains as well as contract farming remains low in Africa.  Farmers with limited land resources are more likely to devote a larger share of their land to low-value crops such as cereals while this pattern weakens with increasing land size and slightly reverses for high-value crops such as spices and herbs.  Smallholders in Egypt face a trade-off between ensuring food security to their house holds and maximizing profit, and land plays a major factor in moderating this trade-off.  Younger and wealthier farmers are more likely to participate in the cultivation of high value crops such as spices and herbs as well as contract farming.  There exist strong complementarities between participation in high-value value chains and contract farming.